Harnessing Chinese hamster ovary cell proteomics for biopharmaceutical processing. (October 2014) - Kumar, Amit; Heffner, Kelley M; Shiloach, Joseph; Betenbaugh, Michael J; Baycin-Hizal, Deniz
Chinese hamster ovary (CHO) cell lines are the preferred host for manufacturing therapeutic proteins. The use of proteomics for recombinant protein production in CHO cells has expanded recently because of the ease in identifying protein levels and its potential to elucidate targets for improved growth and productivity. Coupling advanced analytical methods, labeling strategies and bioinformatics with mass spectrometry-based proteomics facilitates identification and quantification of large numbers of proteins. CHO proteomics studies have increased the knowledge of proteins that affect cell culture events, thereby facilitating media development and cell line engineering to increase growth and production, delay apoptosis and utilize nutrients more effectively. The applications of proteomics offers numerous ways for creating superior hosts and improving biotherapeutics production in CHO cells.